Crossing Borders, Creating Together: An Interdisciplinary Dialogue on Transdisciplinary Knowledge Production - Ulrich Dirnagl; Philipp Misselwitz; Lisa Ruhrort; Dagmar Simon (Historical Social Research, 2021)
Due to the Corona pandemic, it was necessary to cancel the conference "Positionality Reloaded: Dimensions of Reflexivity in the Relationship of Science and Society" at short notice. At the time, in May 2020, it was quite uncertain how far-reaching the consequences of the pandemic would be. This also affected the panel discussion that we had planned in order to collect practical and application-oriented perspectives on transdisciplinarity in academics. As restrictions of traveling and gatherings on social events across the globe intensified, digital conferences gradually developed into an effective format for academic exchange. In this respect, we were thrilled when we were able to save the two-hour panel discussion "Crossing Borders, Creating Together: An Interdisciplinary Dialogue on Transdisciplinary Knowledge Production" on 15 June 2020 using a live video broadcast. The main questions from the conference served as a guide: To what extent do academic publications and knowledge production rely on reflexivity and self-reflection? What consequences does this have for the self-positioning of researchers in the tense relationship between academia and society? The question of how meaningful academic activities are in society and for society correlates directly with the question of the relevance of transdisciplinary research, that is occasionally addressed as a possibility, a demand, a request, or even a necessity. While the other contributions in this collection primarily discuss these questions from a theoretical standpoint, the panel discussion was conceived as an "empirical counterpart." The objective was to explore and discuss the opportunities and challenges that arise in transdisciplinary research practice from different functional perspectives: such as political and mobility research, medicine, or architecture and urban planning. For this purpose, we invited four participants, whom we will introduce below.
Keywords: 300; patient and stakeholder engagement (PSE); evidence-based medicine; clinical trials; meta research; reflexivity; positionality; methodology